122k views
4 votes
Pls help me.
proove it ^​

Pls help me. proove it ^​-example-1
User Racheal
by
5.5k points

1 Answer

5 votes

Answer:

We verified that
a^3+b^3+c^3-3abc=(a+b+c)/(2)[(a-b)^2+(b-c)^2+(c-a)^2]

Hence proved

Explanation:

Given equation is
a^3+b^3+c^3-3abc=(a+b+c)/(2)[(a-b)^2+(b-c)^2+(c-a)^2]

We have to prove that
a^3+b^3+c^3-3abc=(a+b+c)/(2)[(a-b)^2+(b-c)^2+(c-a)^2]

That is to prove that LHS=RHS

Now taking RHS


(a+b+c)/(2)[(a-b)^2+(b-c)^2+(c-a)^2]


=(a+b+c)/(2)[a^2-2ab+b^2+b^2-2bc+c^2+c^2-2ac+a^2] (using
(a-b)^2=a^2-2ab+b^2)


=(a+b+c)/(2)[2a^2-2ab+2b^2-2bc+2c^2-2ac] (adding the like terms)


=(a+b+c)/(2)[2a^2+2b^2+2c^2-2ab-2bc-2ac]


=(a+b+c)/(2)* 2[a^2+b^2+c^2-ab-bc-ac]


=a+b+c[a^2+b^2+c^2-ab-bc-ac]

Now multiply the each term to another each term in the factor


=a^3+ab^2+ac^2-a^2b-abc-a^2c+ba62+b^3+bc^2-ab^2-b^2c-abc+ca^2+cb^2+c^3-abc-bc^2-ac^2]


=a^3+b^3+c^3-3abc (adding the like terms and other terms getting cancelled)


=a^3+b^3+c^3-3abc =LHS

Therefore LHS=RHS

Therefore
a^3+b^3+c^3-3abc=(a+b+c)/(2)[(a-b)^2+(b-c)^2+(c-a)^2]

Hence proved.

User David Liao
by
5.4k points